The effect of low flow anesthesia on hemodynamic and peripheral oxygenation parameters in obesity surgery - Öterkuş, Mesut (Saudi Med J, 2021)
OBJECTIVES: To investigate the effects of low-flow anesthesia on hemodynamic parameters and recovery from anesthesia in obese individuals undergoing laparoscopic surgery. METHODS: This randomized-controlled and prospective study included 44 obese patients who underwent laparoscopic sleeve gastrectomy operation. The patients were randomly allocated into 2 groups as low-flow and high-flow anesthesia. Further, the groups compared in terms of hemodynamic parameters, anesthesia recovery times, operation times, and arterial blood gas parameters. RESULTS: The groups were similar with respect to demographic data. Heart rate, peripheral oxygen saturation, arterial blood pressure measurements, end-tidal, and CO(2), lactate levels measurements were similar in both groups during the entire procedure. There was also no statistically significant difference in terms of arterial blood gas parameters or anesthesia recovery periods. CONCLUSION: Low-flow anesthesia in laparoscopic obesity surgery seems to be safer compared to high-flow anesthesia in terms of the adequacy of tissue perfusion, depth of anesthesia, and postoperative recovery.